Characteristics of the practice of physical activity during a pandemic by COVID-19 in professionals and their families - Enríquez-Reyna, María Cristina; Ceballos Gurrola, Oswaldo; Medina Rodríguez, Rosa Elena; Cocca, Armando; Moreno Muciño, Oddete (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
The objective of the study was to determine the characteristics of the physical activity behavior carried out at the beginning of phase 3 of the epidemiological contingency due to COVID-19 in people over 18 years of age. It is presented a quantitative comparative and cross-sectional study. Two thousand one hundred sixteen professionals affiliated with Physical Education and Sports associations in North, Central and South America participated. In this sample, the main reasons for exercising were physical condition (32.5%), enjoyment (27.8%) and physical appearance (16.3%). More than one in five reported not having time to exercise. There were differences by region and sex for the performance of physical activity during social isolation (p < .05). Even though people recognize the benefits of exercise for health, health is not considered among the main motivations for its performance.